Urging for crisis management paradigm: Deictic expression in Retno Marsudi’s speech at UNGA - Lestari, Wahyu Puji; Mustikareni, Dyah (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
This paper aims to identify the types of deixis and their implications employed by Retno Marsudi’s speech about a new paradigm for the current world crisis during the United Nations General Assembly (UNGA) in September 2022. The researchers employed qualitative descriptive methods to answer the aims of the study. The steps conducted were finding and downloading the video of speech delivered by Retno Marsudi at the UNGA in September 2022 on YouTube, transcribing the speech delivered in the video, collecting the deictic expressions present in the speech transcription, classifying the categories of deictic expressions, and lastly interpreting the purpose of the deixis use according to the content of the speech. The findings indicate that the most used deixis in Retno Marsudi’s speech is Time deixis with 67 occurrences, followed by Person deixis with 55 occurrences, Discourse deixis with 22 occurrences, Social deixis with 5 occurrences, and Place deixis with 1 occurrence. The findings show different outcome with the previous studies concerned with speeches or lectures. It can be implied that Marsudi mostly employed Time deixis because she wanted to emphasize the urgency of her proposed solutions to overcome the world crisis. Furthermore, she wanted to take the audience into thinking about past events as lessons, the current situation as facts happening today worldwide, and the future positive possibilities if Indonesia’s proposed paradigm could be implemented. Hopefully, this paper could help readers to understand the use and implications of deictic expressions found in Marsudi’s speech related to the context.